Agricultural trade interests and challenges at the WTO Ministerial Conference in Buenos Aires: A Southern Cone perspective - Piñeiro, Valeria; Piñeiro, Martín (International Food Policy Research Institute, 2017)
This book focuses on presenting some of the main themes that are pending in the WTO negotiations, with an emphasis on the views and perspectives of the Southern Cone countries. These countries’ interests and perspectives are influenced by the importance of agriculture in their economies and by the important role they play as the largest net food exporters. The book has three Parts in addition to this introduction. The first Part presents the main issues included in the three main Pillars of the Agreement on Agriculture which are still unresolved and that are of special interest for the Southern Cone countries. The second Part presents two themes that, although having been discussed, have not been seriously considered in the WTO deliberations to date – the elimination of export restrictions in food products and the incorporation of environmental disciplines in the WTO agenda. Finally, the third Part presents some conclusions, suggestions, and recommendations.